2020
DOI: 10.1186/s12866-020-01933-1
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between genes encoding virulence factors with antibiotic resistance and phylogenetic groups in community acquired uropathogenic Escherichia coli isolates

Abstract: Background: Antibiotic resistance is an increasing phenomenon in many bacterial pathogens including uropathogenic Escherichia coli. Hypothetical anti-virulent agents could be a solution, but first clear virulence associated gene-pool of antibiotic resistant isolates have to be determined. The aim of this study is to investigate the significant associations between genes encoding VFs with antibiotic resistance and phylogenetic groups in UPEC isolates. Results: The majority of 248 UPEC isolates belonged to phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…Therefore, in this study, we tried to investigate the prevalence of phylogenetic groups, antibiotic resistance genes, and the distribution of these resistance genes and antibiotic resistance patterns in uropathogenic E. coli phylogenetic groups based on the new method of Clermont et al for the first time in Yasuj (Southwest Iran). The results of several studies indicate that extraintestinal pathogenic strains mainly belong to groups B2 and D (to a lesser extent) and, also, the commensal isolates of E. coli belong to groups A and B1 (2,10,22). In the present study, the most common phylogenetic groups belonged to group B2 with a prevalence of 36.4%.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, in this study, we tried to investigate the prevalence of phylogenetic groups, antibiotic resistance genes, and the distribution of these resistance genes and antibiotic resistance patterns in uropathogenic E. coli phylogenetic groups based on the new method of Clermont et al for the first time in Yasuj (Southwest Iran). The results of several studies indicate that extraintestinal pathogenic strains mainly belong to groups B2 and D (to a lesser extent) and, also, the commensal isolates of E. coli belong to groups A and B1 (2,10,22). In the present study, the most common phylogenetic groups belonged to group B2 with a prevalence of 36.4%.…”
Section: Discussionsupporting
confidence: 56%
“…Among them, Escherichia coli is the most common agent that can cause infections at different ages. Studies in different communities have shown that Gram-negative bacilli, especially E. coli, cause more than 80 -90% of infections (1,2). A group of researchers has emphasized that the type of E. coli phylogenetic group plays an important role in their pathogenicity (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have found the positive association between virulence traits including iron scavenger receptors with antibiotic resistance [ 39 , 40 ], there are many contradictions in this regard. For example, in some studies the presence of hly gene was associated with sensitivity to fluoroquinolones [ 41 43 ] and in other study resistance to fluoroquinolones [ 8 ]. Thus, future comprehensive studies are necessary to elucidate the relationship between VFs and antibiotic resistance and the evolutionary direction of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Among variety of VFs, some are generally accepted to be more associated with UPEC [ 7 ]. fim operon, pap operon, and sfa genes encode type I fimbriae, P fimbriae and S fimbriae respectively [ 8 , 9 ]. These structural VFs are the main attachment factors associated with colonization of organism to host cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis comparing plasmids carrying bla genes in this study with plasmid sequences deposited in open databases showed the plasmids in our study were similar with mostly livestock-derived plasmids obtained previously from various countries, but also with human clinical samples, especially from urinary tract infections. pZPK-A41.2-1 carried the P fimbriae encoding virulence gene papC which has been associated with uropathogenic E. coli infections ( Yazdanpour et al, 2020 ). pZPK-A40.2-1 was also similar to a mcr-1 -carrying plasmid isolated from a human urine sample from the United States (GenBank accession: KX276657.1 ), indicating a potential for IncF type plasmids being able to obtain new resistance genes.…”
Section: Discussionmentioning
confidence: 99%